2019
DOI: 10.1002/mds.27695
|View full text |Cite
|
Sign up to set email alerts
|

Genetic silencing of striatal CaV1.3 prevents and ameliorates levodopa dyskinesia

Abstract: Background Levodopa‐induced dyskinesias are an often debilitating side effect of levodopa therapy in Parkinson's disease. Although up to 90% of individuals with PD develop this side effect, uniformly effective and well‐tolerated antidyskinetic treatment remains a significant unmet need. The pathognomonic loss of striatal dopamine in PD results in dysregulation and disinhibition of striatal CaV1.3 calcium channels, leading to synaptopathology that appears to be involved in levodopa‐induced dyskines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
2
30
2
Order By: Relevance
“…In recent work we demonstrated that genetic silencing of striatal Cav1.3 L-type channel in hemi-parkinsonian rats both prevents and reverses LID (Steece-Collier et al, 2019). Cav1.3 has long been appreciated as a key regulator of dendritic spine morphology, including that of MSN, and loss of striatal DA is linked to dysregulation of this channel (Day et al, 2006).…”
Section: A Mechanistic Model Of Nurr1 Activationmentioning
confidence: 97%
“…In recent work we demonstrated that genetic silencing of striatal Cav1.3 L-type channel in hemi-parkinsonian rats both prevents and reverses LID (Steece-Collier et al, 2019). Cav1.3 has long been appreciated as a key regulator of dendritic spine morphology, including that of MSN, and loss of striatal DA is linked to dysregulation of this channel (Day et al, 2006).…”
Section: A Mechanistic Model Of Nurr1 Activationmentioning
confidence: 97%
“…Supporting this idea, in a recent study, a genetic silencing of striatal CaV1.3 voltage‐gated L‐type calcium channels was found to completely prevent LID in severely parkinsonian rats and to ameliorate pre-existing severe LID. 103 …”
Section: Pathophysiological Mechanisms Of Lidmentioning
confidence: 99%
“…Supporting this idea, in a recent study, a genetic silencing of striatal CaV1.3 voltage-gated L-type calcium channels was found to completely prevent LID in severely parkinsonian rats and to ameliorate pre-existing severe LID. 103 All the events described in this section (Figure 2) contribute to pathological changes in neuronal firing patterns, which in turn lead to excessive disinhibition of thalamocortical neurons and overactivation of cortical motor areas, and ultimately determine LID development. 17,18…”
Section: Other Mechanismsmentioning
confidence: 99%
“…In advanced PD, however, symptom control is hampered by the fact that a single dose of medication triggers dyskinesia more easily and lasts for a shorter period of time. Presynaptic mechanisms can explain some features of these motor fluctuations but not their induction by dopamine receptor agonists [3,4].…”
Section: Introductionmentioning
confidence: 96%